Bentuk Pelayanan Pendidikan Inklusi di KB dan TK: Studi Kasus di KB dan TK Hamemayu - Ulfa, Mutia (ACIECE, 2019)
Lately Indonesia tried to make inclusive education policy, that every child in any backwardness still have the same rights and obligations in education. Since the purpose of education is educating the nation, regardless of any side. The research method is to use to describe the results of qualitative research findings and analysis of data using interviews, observation and documentation were then analyzed with a model of Miles and Huberman. One of the schools which implement inclusive education is kindergarten KB hamemayu that in this study described some form of service used in kindergarten KB hamemayu in good inclusive education for children with special needs and also for normal children who are in regular schools